Characterisation of non-coagulating milk and effects of milk composition and physical properties on rennet-induced coagulation in Swedish Red Dairy Cattle. (August 2019) - Nilsson, Kajsa; Stålhammar, Hans; Stenholdt Hansen, Mikka; Lindmark-Månsson, Helena; Duchemin, Sandrine; Fikse, Freddy; de Koning, Dirk Jan; Paulsson, Marie; Glantz, Maria
Abstract: Non-coagulating milk is a serious problem in the cheese industry, since it decreases cheese yield, resulting in decreased economic output. This study evaluated rennet-induced coagulation properties and composition of milk from individual Swedish Red Dairy Cattle. Milk samples from 679 individual cows were rheologically evaluated, of which 18.1% of the cows produced non-coagulating milk and 18.9% produced poor-coagulating milk. This resulted in 37% of the milk samples being non-optimal in cheese production, which is an alarmingly high figure. A comparison between non-coagulating and coagulating milk showed a significantly lower calcium content and less free Ca 2+ in non-coagulating milk. The results provide more information about non- and poor-coagulating milk and will be further used to understand the genetic background of non-coagulating milk and breed against this undesired milk property.